1974
DOI: 10.1073/pnas.71.9.3701
|View full text |Cite
|
Sign up to set email alerts
|

13 C Nuclear Magnetic Resonance Spectroscopy of Native and Recombined Lipoproteins

Abstract: ABSTRACT13C nuclear magnetic-resonance data on native and recombined lipoproteins are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Its location in the bilayer has been of particular interest, and suggestions have been made that the polar hydroxyl moiety on the cholesterol interacts with possibly the N-methyl region, or the phosphate region, or the carbonyl region where the fatty acid chains are esterified to the glycerol. Cholesterol does not affect the T1 relaxation times of the N-methyl headgroup protons or carbon atoms (26,27). These results suggest that the effect of the cholesterol OH group on trimethylammonium group motion is negligible.…”
Section: Discussionsupporting
confidence: 53%
“…Its location in the bilayer has been of particular interest, and suggestions have been made that the polar hydroxyl moiety on the cholesterol interacts with possibly the N-methyl region, or the phosphate region, or the carbonyl region where the fatty acid chains are esterified to the glycerol. Cholesterol does not affect the T1 relaxation times of the N-methyl headgroup protons or carbon atoms (26,27). These results suggest that the effect of the cholesterol OH group on trimethylammonium group motion is negligible.…”
Section: Discussionsupporting
confidence: 53%
“…3, 5, 8, 9, 10, and 12: Reassembled lipoproteins isolated as infranatant fraction (3 ml) after ultracentrifugation at density 1.063 g/ml. HDL(2) *: native HDL labeled in its cholesterol ester moiety using 1,2-[dioleoyl-1-_4C]-sn-phosphatidylcholine as substrate for lecithin-cholesterol-acyltransferase (24).…”
Section: Resultsmentioning
confidence: 99%
“…Godici & Lansberger (130) have measured ~3C Tl's and linewidths for phospholipids in the presence of the cholesterol, and also suggested that cholesterol decreases the long range swinging of the acyl chains. The effects of protein on phospholipid motion have also been investigated with ~3C NMR using recombinant lipoprotein/lipid dispersions (131)(132)(133). These studies suggest that lipid-protein interactions are primarily hydrophobic in nature rather than ionic (131,133), and that lipids interacting with protein arc somewhat less mobile than in pure lipid systems (132).…”
Section: Future Prospectsmentioning
confidence: 99%